Strategic Optimization of Hospital Health Services under the National Health Insurance (JKN) Era - Wahyu Kusuma, Kristiana; Agung Mulyaningsih, Erika; Pitriawati, Dewi; Rachmadhani, Yuannisa (Yayasan Meira Visi Persada, 2025)
This study explores strategic efforts to optimize hospital health services in Indonesia within the framework of the National Health Insurance (Jaminan Kesehatan Nasional, JKN). Since its launch in 2014, JKN, administered by BPJS Kesehatan, has aimed to ensure equitable access to healthcare. However, implementation challenges such as limited medical infrastructure, shortages in human resources, and financial sustainability have constrained service quality in hospitals. Employing a literature review methodology, this research analyzed twelve peer-reviewed articles published between 2015 and 2025, focusing on strategic responses of hospitals to JKN demands. The review identifies five primary strategies: (1) leveraging hospital management information systems (SIMRS) to enhance operational efficiency, (2) optimizing digital tools such as the Mobile JKN application to improve patient satisfaction and service accessibility, (3) reassessing premium subsidy policies based on participants’ financial capacity to ensure budgetary efficiency, (4) strengthening service quality to build patient loyalty, and (5) addressing service gaps through human resource development, especially in empathy and communication. Findings underscore the importance of integrating technology, improving administrative and clinical workflows, and tailoring financial policies to real-world economic conditions. Additionally, continuous training and performance evaluation are recommended to align hospital operations with JKN standards. The study contributes a synthesized perspective on how Indonesian hospitals can effectively adapt to JKN, highlighting actionable strategies to improve healthcare delivery in a resource-constrained setting.